Development of an Arabic language curriculum based on the deep learning approach - Multazam Syifa; Fatur Fahrezi; Muhajir Muhajir (Curricula: Journal of Curriculum Development, 2025)
The Arabic language curriculum in Indonesia is still dominated by traditional approaches, so it requires a modern approach that accelerates students' abilities. This study aims to examine the development of an Arabic language curriculum based on a deep learning approach as a response to the dominance of traditional approaches that focus on memorizing grammar and vocabulary. The method used is a literature study with a descriptive-analytical approach. Data sources were obtained from various academic databases, such as DOAJ, with publications ranging from 2020 to 2025. The focus of the study was on the integration of deep learning, Bloom's Taxonomy, and SOLO Taxonomy in the context of implementing the Merdeka Curriculum. The results of the study indicate that this approach enables the creation of more contextual and applicable Arabic language learning. Key findings include: the integration of Bloom's Taxonomy facilitates the formulation of learning objectives from the recall level to the creation level, SOLO Taxonomy is effective in evaluating the depth of students' understanding, and the implementation of project-based learning. This study concludes that the deep learning approach has the potential to transform the Arabic language curriculum into one that is more humanistic and aligned with the profile of Pancasila learners.   Abstrak  Kurikulum pembelajaran bahasa Arab di Indonesia masih didominasi oleh pendekatan tradisional, maka dari itu memerlukan pendekatan modern yang mempercepat kemampuan peserta didik. Penelitian ini bertujuan untuk mengkaji pengembangan kurikulum Bahasa Arab berbasis pendekatan deep learning sebagai respons terhadap dominasi pendekatan tradisional yang berfokus pada hafalan tata bahasa dan kosakata. Metode yang digunakan adalah studi pustaka dengan pendekatan deskriptif-analitis. Sumber data diperoleh dari berbagai basis data akademik seperti DOAJ dengan rentang publikasi antara tahun 2020 hingga 2025. Fokus kajian diarahkan pada integrasi deep learning, Taksonomi Bloom, dan Taksonomi SOLO dalam konteks implementasi Kurikulum Merdeka. Hasil kajian menunjukkan bahwa pendekatan ini memungkinkan terciptanya pembelajaran Bahasa Arab yang lebih kontekstual dan aplikatif. Temuan utama meliputi: integrasi Taksonomi Bloom memfasilitasi perumusan tujuan pembelajaran dari level mengingat hingga mencipta, Taksonomi SOLO efektif mengevaluasi kedalaman pemahaman peserta didik, dan implementasi pembelajaran berbasis proyek. Penelitian ini menyimpulkan bahwa pendekatan deep learning berpotensi mentransformasi kurikulum Bahasa Arab menjadi lebih humanistik dan relevan dengan profil pelajar Pancasila.  Kata Kunci: kurikulum bahasa Arab; kurikulum merdeka; pendekatan deep learning; taksonomi Bloom; taksonomi SOLO